(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Two new species of Dryinidae (Hymenoptera: Chrysidoidea) from Argentina are described: Gonatopus cuyanus, from Mendoza, and Esagonatopus minuslamellatus, from Corrientes. The males of the following species, previously known only on the basis of female specimens, are described: Gonatopus doellojuradoi (Ogloblin), G. silvestrii Kieffer, G. fritzi (Olmi), G. hilaris Olmi and G. autumnalis Olmi. Trichogonatopus raptor (Fenton) and Gonatopus fiavoides (Olmi) were cited for the first time in Argentina. New keys to the females of the Neotropical species of Esagonatopus and the males of the Neotropical species of Gonatopus are presented.